THE NEGATIVE IMPACT OF ETHNIC CONFLICT OR NATIONALISM ON THE SOCIO-POLITICAL STABILITY AND PROGRESS OF SOCIETY - Olmos Toshev (European Journal of Interdisciplinary Research and Development, 2023)
This article analyzes the fact that effectively combating the threat of nationalism and ethnic conflicts on various socio-political grounds has become a global problem today. It is also revealed that the aggravation of interethnic conflicts in certain countries or regions can lead to a weakening of social and political stability in society and the intensification of extremist and nationalist processes.